1997
DOI: 10.1006/cbir.1998.0166
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular Metals: Quantification and Mapping by Complementary Techniques

Abstract: Metal-replete cuticle was characterised by back-scattered electron imaging, secondary ion mass spectrometry, proton induced X-ray emission and SEM-X-ray microanalysis. Each technique was found to have singular advantages and limitations for localising and quantifying metal content. Manganese and zinc were found coincident at the mandibular cutting edge of the leaf-cutting ant Atta sexdens; these two metals were found in different zones within jaws of the ragworm, Nereis virens; while only manganese was found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Pollinator fig wasps have a spoon-like structure in contrast to the sharp and long ovipositors with teeth-like projections at the parasitoid ovipositor tip that are probably adapted for oviposition. Earlier studies examined the ovipositor morphology in various parasitic Hymenoptera and suggested that many morphological features in ovipositor structures are matched to specific host types (Quicke et al, 1999;Rahman et al, 1998;Fawke et al, 1997;Broad and Quicke, 2000;LeRalec et al, 1996). These studies also showed the presence of transition metals, such as zinc, manganese and calcium, in the tips of the ovipositors using X-ray microanalysis.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Pollinator fig wasps have a spoon-like structure in contrast to the sharp and long ovipositors with teeth-like projections at the parasitoid ovipositor tip that are probably adapted for oviposition. Earlier studies examined the ovipositor morphology in various parasitic Hymenoptera and suggested that many morphological features in ovipositor structures are matched to specific host types (Quicke et al, 1999;Rahman et al, 1998;Fawke et al, 1997;Broad and Quicke, 2000;LeRalec et al, 1996). These studies also showed the presence of transition metals, such as zinc, manganese and calcium, in the tips of the ovipositors using X-ray microanalysis.…”
Section: Research Articlementioning
confidence: 99%
“…The ovipositors of wood-boring wasps show little evidence of wear and tear of their cutting parts . It is hypothesized that the presence of zinc and manganese hardens the insect cuticle and permits it to cut through hard substrates such as wood Hillerton and Vincent, 1982;Fawke et al, 1997). However, the distribution of metals in insect ovipositors and their direct correlation with local material properties has not been explored to date.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Arthropod jaw tissues may also contain impressive metal levels, in particular Zn or Mn as first shown by Hillerton and Vincent [48]; published metal contents are summarized in Table 1. The leaf-cutter ant is one of the best studied systems [49,50] with mandibles exhibiting a range of serrations at the cutting edge enriched in Zn (Figure 8b) [49]. The Zn content gradually decreases from the cutting edge towards the trailing part ( Figure 8c).…”
Section: Zinc and Manganese In Arthropodsmentioning
confidence: 99%
“…In arthropod mandibles and ovipositors, Zn and Mn appear to be separate in most cases even in species that contain both elements. One exception is given by the mandibular teeth of the leaf-cutter ant, where secondary ion mass spectrometry (SIMS) data show at least partial co-localization event though the Mn concentration is 20 times smaller than that of Zn [50]. The separate use of Zn [49].…”
Section: Zinc and Manganese In Arthropodsmentioning
confidence: 99%